1984
DOI: 10.1111/j.1365-2141.1984.tb02918.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Pitted’ erythrocytes: impaired formation in splenectomized subjects with congenital spherocytosis

Abstract: 'Pitted' erythrocyte counts are widely used in the quantitative assessment of functional hyposplenism and in the prediction of recurrence of splenic function in splenectomized subjects. Both of these functions require counts from electively splenectomized controls for comparison. The 'pitted' erythrocyte counts in patients splenectomized for congenital spherocytosis are lower than those found in subjects whose spleens were removed electively for other reasons. This appears to be due to the specific membrane de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1984
1984
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…We noted elevated pocked erythrocyte counts in patients with hereditary spherocytosis after splenectomy, and the values were no different than those observed in other asplenic individuals. We are unable to explain why the findings of O'Grady et a1 [3] differ from ours. Since the erythrocytic vesicles that characterize the pocked erythrocyte are felt to represent autophagic vacuoles accumulating during red cell aging [ 121, one would not necessarily expect a primary membrane defect like hereditary spherocytosis to significantly affect this process.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…We noted elevated pocked erythrocyte counts in patients with hereditary spherocytosis after splenectomy, and the values were no different than those observed in other asplenic individuals. We are unable to explain why the findings of O'Grady et a1 [3] differ from ours. Since the erythrocytic vesicles that characterize the pocked erythrocyte are felt to represent autophagic vacuoles accumulating during red cell aging [ 121, one would not necessarily expect a primary membrane defect like hereditary spherocytosis to significantly affect this process.…”
Section: Discussioncontrasting
confidence: 79%
“…O'Grady and co-workers [3] recently reported that among 15 patients with hereditary spherocytosis, 13 had pocked erythrocyte counts within the normal range. These normal pocked erythrocyte values, in spite of the asplenic state, were attributed to failure of the red blood cells to form vacuoles as a consequence of the primary erythrocyte membrane defect in hereditary spherocytosis [3]. Pocked erythrocyte counts in patients with hereditary spherocytosis prior to splenectomy were not studied by these workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Grady et a1 (13) demonstrated that splenectomized patients with congenital spherocytosis had considerably lower counts of pitted erythrocytes than patients splenectomized for other reasons. This finding contrasts with earlier reports (2,14).…”
mentioning
confidence: 99%